Short - term Fiscal Needs vs. Long - term Sustainable DevelopmentWHAT IS, AND WHAT SHOULD BE DONE TO FACILITATE AN OPEN FREIGHT MARKET FREE OF DISTORTED COMPETITIVE CONDITIONS - Sip, Emanuel (Transactions on Transport Sciences, 2008)
The following keynote text is to respond to the following fundamental questions: a. What are the existing activities to facilitate an open freight market free of distorted competitive conditions? b. What provisions are governments making for investment in rail infrastructure? c. How do transportation policy makers need to revise their strategies to satisfy EC goals? At the moment, a majority of goods are carried on Europe's roads, even if it brings about grave global problems. This is the main reason for the constant drive to internalize the external costs of road transport pursuing the 'user pays' and 'polluter pays' principles. The recently published Greening Transport Initiatives of the European Commission, especially the amendment of the Eurovignette Directive, are a good step in this direction, even if they evoked a scope of different views aminy stakeholders. Also other initiatives of the Commission, such as the Freight Transport Logistics Action Plan, will lead to a better utilization of transport infrastructure and enhanced support of more sustainable transport modes. The Commission, as well as individual Member States alone or in cooperation with other interested partners, undertakes actions improving the existing rail infrastructure to be utilized by freight transport. New rail transport axes are sometimes at the top of cutting-edge technology and generally designed to host both freight and passenger rail transportation. The text brings some examples of such projects, which are being carried out in the 'new' EU countries, also with the help of European funds. So as to satisfy EC goals, the transportation policy makers need to revise their strategies in a double direction: towards active participation on implementing new Commission initiatives aimed at levelling the playing field between transport modes, and towards improving their domestic rail markets and correcting shortcomings in the implementation of the First Rail Package, so that rail freight should be able to regain and extend its market position also 'by its own force'.
Keywords: Rail freight transport; internalization of external costs; Eurovignette Directive; Freight Transport Logistics Action Plan; rail infrastructure; European funds; First Railway Package; conflicts of interests.